Estudo e implementação de um conversor bidirecional como interface na regulação de tensão em barramento c.c. e carregamento de baterias em um sistema nanorrede - Waner Wodson Aparecido Gonçalves Silva (2013)
Due to the increase of electricity demand to attend the growing needs of society and to compensate deficiencies of the energy generation, there is a need to enhance the participation of renewable energy resources into the energy matrix, since conventional fossil energy sources will not be able to supply this increasing energy demand owing to environmental con-strains. The smart grids introduce new concepts for the electrical power system, such as mi-cro and nanogris, in which the power generation is based on renewable resources like wind and solar power. The energy production in such systems depends on natural factors as solar irradiation and wind speed, what requires the employment of local energy storage systems, based normally on batteries, in order to ensure uninterrupted power supply to the local power system, or nanogrid. In this thesis, a study is conducted over a bidirectional dc-dc converter, which inter-faces the energy storage system and the main dc bus of a dc nanogrid. This power converter will control the power flow between the nanogrid and the battery banks, hence providing a regulated dc voltage on the nanogrid side. The dc nanogrid architecture is presented and the bidirectional dc-dc converter topologies revised, thus enabling the selection of the Dual Ac-tive Bridge structure as the interface converter. A set of modulation techniques were studied in order to decide which one is more suitable for employment on an experimental converter. A control method is proposed which provides means for ensuring a regulated voltage on the nanogrid main dc bus and concomitantly respects the battery bank charging restrictions.